Documentación de los Procesos de Compra de Cacao, Para el Incremento de la Productividad en "Industrial Cacotera del Huila S.A. Tolimax S.A." - Calidad en las Compras de Cacao - Carrera Vargas, Marco Antonio (Universidad Antonio Nariño, 2021)
The constant changes that exist in the business, industrial and commercial field, require that productive companies have to adapt to these changes in trends and tastes demanded by the market, which go hand in hand with globalization and economic tightening, in order to attract new customers and retain current ones, they see the obligation and need to develop and implement new market strategies and models for the optimization and standardization of production processes, giving rise to the productivity, efficiency and performance of material resources , technological and human, as the study of documentation of the cocoa purchase processes was carried out in the company Industrial Cacaotera del Huila SA- Tolimax SA